A critical assessment of nutrition labelling and determinants of its use and understanding - Cannoosamy, Komeela; Jeewon, Rajesh (Progress in Nutrition, 2016)
Abstract Over the years, nutritional information on food packages has gained popularity among food manufacturers and consumers due to increasing consumer interest in health and diet issues. Nutrition labels acts as both a marketing tool for food manufacturers and is a source of information for the purchaser. It acts as a regulatory mechanism whereby consumers are protected and fair trading is encouraged. Despite its importance in assisting consumer in making informed dietary choices, nutrition labelling is not mandatory in all countries. There is a strong need for the development of a harmonised regulatory framework with stakeholders of nutrition labelling involved. Also, the effectiveness of nutritional labels is dependent on individual characteristics, health-related factors, and situational, attitudinal and behavioural factors. Numerous studies have investigated factors influencing nutrition labelling use and while some findings corroborated each other, others reported opposite findings. Possible ways to promote use and understanding of nutrition labels would be to present it in an appropriate format together with nutrition education being carried out for any nutritional information provided. This paper aims to critically assess the types of nutritional information provided, the regulatory issues and the research work carried out on its determinants of use and understanding.